Dissecting Cellular Function and Distribution of β-Glucosidases in Trichoderma reesei - Ai-Ping Pang (American Society for Microbiology, 2021)
Although β-glucosidases play an important role in fungal cellulase induction and production, our current understanding does not provide a global perspective on β-glucosidase function. This work comprehensively studies all the β-glucosidases regarding their effect on cellulase production and their cellular distribution and secretion.